Distinct laminar origins of sensory-evoked high-gamma and low-frequency ECoG signals revealed by optogenetics - Pierre-Marie Garderes; Daniel E. Feldman; Kristofer E. Bouchard (Proceedings of the National Academy of Sciences, 2026)
Electrocorticography (ECoG) provides a high-spatiotemporal-resolution measure of cortical activity (cortical surface electrical potentials, CSEPs) in humans and animals. The CSEP high-gamma band (Hγ, 65 to 170 Hz) correlates with neuronal firing rates at the columnar spatial scale and is widely used as a biomarker of local activity. Whether Hγ reports all stages of columnar processing, intermediate processing in L2/3 (close to the ECoG electrode), or the main columnar output in L5, is unknown. We disentangled the laminar origins of Hγ and other ECoG bands by optogenetically suppressing L2/3 or L5 pyramidal cells during micro-ECoG recording in the mouse somatosensory cortex. Whisker deflections evoked transient, topographically localized CSEPs. L5 optogenetic suppression most strongly reduced 65 to 450 Hz (Hγ-uHγ) bands in sensory-evoked ECoG signals, whereas L2/3 suppression most strongly reduced 4 to 27 Hz (θ-β) bands. Thus, different CSEP frequency bands reflect layer-specific activity and are biomarkers of distinct stages of sensory-evoked columnar processing.